2020
DOI: 10.2147/ijn.s235832
|View full text |Cite
|
Sign up to set email alerts
|

<p>Liquiritigenin-Loaded Submicron Emulsion Protects Against Doxorubicin-Induced Cardiotoxicity via Antioxidant, Anti-Inflammatory, and Anti-Apoptotic Activity</p>

Abstract: Background: The clinical use of doxorubicin (DOX) is severely limited due to its cardiotoxicity. Thus, there is a need for prophylactic and treatment strategies against DOX-induced cardiotoxicity. Purpose: The purpose of this study was to develop a liquiritigenin-loaded submicron emulsion (Lq-SE) with enhanced oral bioavailability and to explore its efficacy against DOX-induced cardiotoxicity. Methods: Lq-SE was prepared using high-pressure homogenization and characterized using several analytical techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The occurrence of this disease is correlated to multiple factors of cell proliferation, metastasis, apoptosis, tumor microenvironment, and autoimmune system. TCM therapies have been widely introduced in treating cancer, acting on diverse signal transduction pathways with few adverse reactions [ 36 ]. The traditional Chinese medicine nightshade has been reported that it can play an anti-tumor role by inhibiting cell adhesion, tumor cell infiltration and metastasis, and improving the immune function of the body [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of this disease is correlated to multiple factors of cell proliferation, metastasis, apoptosis, tumor microenvironment, and autoimmune system. TCM therapies have been widely introduced in treating cancer, acting on diverse signal transduction pathways with few adverse reactions [ 36 ]. The traditional Chinese medicine nightshade has been reported that it can play an anti-tumor role by inhibiting cell adhesion, tumor cell infiltration and metastasis, and improving the immune function of the body [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liquiritigenin (Lq) (Figure 1) is a flavonoid in Glycyrrhizae radix (licorice) widely used as a traditional Chinese medicine. A recent study underscored its protective effects against doxorubicin‐induced cardiotoxicity and cardiac injury induced by high fructose‐feeding (Shi et al, 2020; Xie, 2017). Lq can ameliorate myocardial fibrosis in mice (L. Li, Fang, Yu, Liu, & Yang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a dihydroflavonoid compound, LQ exerts certain effects on the cardiovascular system and nervous system. In addition, it functions in antivirus, antioxidant, antitumor, and other pharmacological effects [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%